Ethical fundamentals of doing small business in Russia - S. A. Sidorova (Путеводитель предпринимателя)
The article mentions the need for development of small business in Russia based on the principals of perfect competition market from the point of view of the business ethics development. At the same time, the role of the government is a «night-watchman». Now Russian small business isn’t developed because of the system ofprinciples that Russia inherited from the USSR.